2022
DOI: 10.3390/ma15176012
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Hydrogen Reduction of a Lime-Added Bauxite Residue Agglomerate at Elevated Temperatures for Iron and Alumina Recovery

Abstract: The hydrogen reduction of bauxite residue lime pellets at elevated temperatures was carried out to recover iron and alumina from the bauxite residue in a new process route. Prior to the H2 reduction, oxide pellets were initially prepared via the mixing of an industrial bauxite residue with fine calcite powder followed by calcination and high-temperature sintering. The chemical, compositional, and microstructural properties of both oxide and reduced pellets were studied by advanced characterization techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…During the Na 2 CO 3 leaching process, Na + and CO 3 −2 from the bulk solution moved to the matrix interface, where the matrix is mostly composed of metallic iron and mayenite. Here, the assumption is that, in the reduced pellets along with metallic iron and mayenite, other phases such as perovskite and larnite are present; however, those phases are stable during alkali leaching [10]. The reaction of Na + with mayenite occurs on the surface of mayenite and NaAlO 2 is leached out from the pellets to the bulk solution, leaving behind CaCO 3 on the reduced pellets.…”
Section: Thermochemistry Of Process and Reaction Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the Na 2 CO 3 leaching process, Na + and CO 3 −2 from the bulk solution moved to the matrix interface, where the matrix is mostly composed of metallic iron and mayenite. Here, the assumption is that, in the reduced pellets along with metallic iron and mayenite, other phases such as perovskite and larnite are present; however, those phases are stable during alkali leaching [10]. The reaction of Na + with mayenite occurs on the surface of mayenite and NaAlO 2 is leached out from the pellets to the bulk solution, leaving behind CaCO 3 on the reduced pellets.…”
Section: Thermochemistry Of Process and Reaction Mechanismsmentioning
confidence: 99%
“…Iron and alumina recovery has been studied by Skibelid et al (2022), and they studied the hydrogen reduction in BR-calcite sintered pellets at various temperatures followed by alkali leaching for alumina recovery. They found that at a reduction temperature of 1000 • C, all iron oxides were converted to metallic iron and the alumina recovery went above 87% during the alkali leaching [10]. An amount of alumina is lost in the form of complex phases such as gehlenite, which forms during the sintering and reduction of the pellets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen reduciton of the lime fluxed BR pellets can be done in isothermal and non-isothermal regimes. Results from isothermal reduction regime is presented in reference [9] and this study presents results from non-isothermal reduction regime.…”
Section: Introductionmentioning
confidence: 99%
“…Following the leaching process, the residue became enriched with calcite and rare earth elements. This enriched calcite residue was subsequently recycled to produce bauxite residue calcite pellets, completing a sustainable materials loop within the process [12,13].…”
Section: Introductionmentioning
confidence: 99%